(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this study is to present the surgical, oncologic and functional results of the first 34 robotic radical prostatectomy (RARP) procedures performed in our clinic.Material and Methods: Data of 34 patients who underwent RARP between July 2017 and October 2019 were evaluated.Results: The mean patient age was 58.73±4.94 years, and the mean preoperative serum prostate-specific antigen level was 8.9±2.07 ng/mL. Bilateral neurovascular bundle (NVB) sparing, unilateral NVB-sparing, and non-NVB-sparing surgery were performed in 7.5, and 22 cases, respectively. The mean prostate weight was 58.73±26.03g. Anterior reconstruction suture was performed in 22 (64.7%) cases. Mean console time, intraoperative blood loss, duration of hospital stay, and urethral catheter removal time were 195.2±14.03min, 120.3±21.2cc, 7.34±1.62 days, and 7.26±1.26 days, respectively. Biochemi¬cal recurrence was observed in two patients, one of whom received maximal androgen blockage (MAB), and the other one received pelvic radiotherapy+MAB. All the patients with at least one-year follow-up were fully continent (0 pads/day). Of the 16 (47%) patients with no preoperative erectile dysfunction (ED) and with at least three-month follow-up, 9 (62.5%) had no ED, with or without any additional medica¬tion including phosphodiesterase-5 (PDE5) inhibitors. Conclusion: RARP is a safe minimally invasive procedure with acceptable morbidity, excellent operative, pathological and oncological outcomes, and satisfactory functional results.